If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + 6b = -2 Solving 5a + 6b = -2 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6b' to each side of the equation. 5a + 6b + -6b = -2 + -6b Combine like terms: 6b + -6b = 0 5a + 0 = -2 + -6b 5a = -2 + -6b Divide each side by '5'. a = -0.4 + -1.2b Simplifying a = -0.4 + -1.2b
| 6a+b=-2 | | 3x-8=-2-3x | | -5r-5s=25 | | b+14=56 | | 8x+2(1.5x)=400 | | 4r+s=-14 | | (6x-20)= | | -7x+11=60 | | -2x-4=-x+0 | | (t+3)(t+8)=t(t+5)+168 | | 18-2z=6-4 | | -6y=36x-72 | | 2x^3+4x^2+10x=0 | | 7x-2=34+x | | 4y+7y=66 | | 5n+10-8=2x | | 13a+50=360 | | 2(x-7)+3(x-1)=4+3 | | 4x+4y=-32 | | X+18=-4 | | 2y^2-7=25 | | x-4/8=15 | | -3(8x+2)+4(5x-1)= | | (3x^2y-xy)dx+(2x^3y^2+x^3y^4)dy=0 | | 3/5x-4=2 | | x-14=66 | | -5x-6=x-48 | | 4(-5x+8)-(x+5)=-15 | | 9xm+19=55 | | 4(-3x-6)= | | m(m-7)= | | 2*x-7=1 |